Bollywood’s representation of Shakespeare, a postmodern Study: Macbeth-Maqbool ,Othello-Omkara, Hamlet- Haider - Rahman, Rezwana (BRAC University, 2018)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master of Arts in English, 2017.